Er:YAG laser-assisted filtration surgery: initial results in rabbits - Kapelushnik, Noa; Leshno, Ari; Singer, Reut; Huna-Baron, Ruth; Barkana, Yaniv; Skaat, Alon (BMC ophthalmology, 2021)
Background Glaucoma is a leading cause of global blindness, especially preventable blindness. The increased prevalence of glaucoma has led to a growing demand for newer, safer, more rapid, and simpler treatments for the reduction of intraocular pressure (IOP). In this study, we evaluated the safety and feasibility of performing filtration glaucoma surgery with an Ab-Interno Er:YAG laser in rabbits. Methods Nine New Zealand White rabbits age 16 weeks were studied. After subconjunctival injection of mitomycin C (MMC), a novel Ab-Interno Er:YAG laser probe was inserted into the anterior chamber (AC) through a clear corneal 1 mm paracentesis and directed at the trabecular meshwork adjacent to the MMC injection area. A pulsed laser beam was applied to create a patent sclerostomy connecting the AC to the subconjuctival space, resulting in a filtering bleb. The laser system used was the Er:YAG laser system - LAS25-FCU, (Pantec Biosolutions AG, Liechtenstein). Parameters used: Wave lengh: 2940 nm, Pulse length: 100–400 μsec,frequency: 250 Hz. Average laser power in accordance to the fiber tip diameter: 0.85 W(range 0.8–0.92 W). Complete ocular exams, including IOP measurements, were performed on 1, 7, 14, and 23 days postoperatively. Three rabbits were sacrificed on days 1, 14, and 23, and histological examinations were performed on all nine eyes. Results All procedures resulted in a functional medium-large superior bleb without significant complications. The bleb was sustained in all rabbits by day 14 and in one of the three rabbits that reached the last follow-up at 23 days. No cases of postoperative hypotony were observed. There was a transient significant reduction in mean IOP on postoperative days 5 and 7 ( P = 0.028). Histopathological analysis revealed a patent full-thickness scleral tunnel with only a minor degree of surrounding coagulation necrosis. Conclusions The Ab-Interno laser sclerostomy procedure is potentially safe and effective based on initial experience in an in-vivo rabbit animal model.